2003
DOI: 10.1046/j.1540-8175.2003.03037.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perindopril on Left Ventricular Global Performance During the Early Phase of Inferior Acute Myocardial Infarction: Assessment by Tei Index

Abstract: Global LV function (DI) is impaired in patients with AMI-I. Administration of perindopril has a favorable impact on LV performance in patients with AMI-I, achieved through improvement of the diastolic function (IRT), which indirectly improves LV systolic function (ET, DI). This beneficial influence of perindopril is the result of the direct tissue effect of the drug and not its hemodynamic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(97 reference statements)
4
6
0
Order By: Relevance
“…These data are consistent with the results of previous studies in AMI patients [22,23] or studies evaluating time intervals in MI [26,27]. Treatment with irbesartan induced significant shortening of isovolumetric contraction time and prolongation of ejection time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data are consistent with the results of previous studies in AMI patients [22,23] or studies evaluating time intervals in MI [26,27]. Treatment with irbesartan induced significant shortening of isovolumetric contraction time and prolongation of ejection time.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that the treatment with Irbesartan likely resulted shortly to the restoration of global LV function after a first limited AMI. This latter finding is in accordance with recent studies [22,28] documenting the improvement of overall LV function in AMI patients with [28] or without [22] LV systolic dysfunction, after administration of either ACE inhibitors [22,28] or AT-1 receptors inhibitors [28]. It seems that independently from LV systolic function of AMI patients, blocking of harmfull effects of angiotensin II at any stage, possibly leads to a significant improvement of the global LV function.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies show that β-blockers, in addition to ACE inhibitors or ARBs, have beneficial effects on left ventricular remodeling [29]. Nearchou et al [30] reported that ACE inhibitor therapy improved ventricle performance and Tei index during the early phase of inferior acute myocardial infarction. However, in our study, there was no significant difference in the medications.…”
Section: Discussionmentioning
confidence: 99%